Effect of Thermal Treatment on the Extraction and Antioxidant and Antiglycation Activities of (Poly)phenols from Ribes magellanicum - Felipe Ávila; Natalia Martinez; Nicolás Mora; Katherine Márquez; Felipe Jiménez-Aspee (Molecules)
Phenolic compounds have antiglycation activity, but the changes occurring during thermal treatment (TT) in these activities are not completely understood. The effects of the extraction conditions of (poly)phenols from Ribes magellanicum fruits, before and after TT, on their antioxidant and antiglycation effects were assessed. (Poly)phenol-enriched extracts (PEEs) from raw and TT (90 °C, 1 h) Ribes magellanicum were extracted using three solvent mixtures (ethanol/water/acetic acid) with increasing water content (0, 24, and 49%) and three solvent-to-solid ratios (5, 10, and 20 mL/g). PEEs of raw samples showed increased values of total (poly)phenols (TPC), TEAC, and FRAP and decreased IC50 values of fluorescent advanced glycation end products (AGEs) with increasing water content. An increase in TPC and FRAP values was observed for TT samples, but an increase in the IC50 values of fluorescent AGEs for PEEs with increasing water content was observed. Antiglycation activity (IC50 raw/IC50 TT) depended on the solvent-to-solid ratio and the extracting solvent. HPLC-DAD-MS analysis of raw and TT samples showed degradation of anthocyanins, flavonoid fragmentation, and oxidation as the main changes in the phenolic composition of TT samples. We show that TT affects the (poly)phenolic composition of R. magellanicum, producing a decrease in the antiglycation activity when extractions are performed with increasing water content, despite increasing TPC and FRAP activity.